Penerapan Pembelajaran Multirepresentasi Berbasis Lesson Study untuk Meningkatkan Hasil Belajar Mahasiswa pada Mata Kuliah Program Linier - Sri Irawati; Agus Subaidi (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2018)
The aim to be achieved in this study was to determine the increase in activity and student learning outcomes in the application of lesson study based multi-representational learning in linear program subjects. The type of research is class action research which consists of the steps of preparation, implementation, observation and reflection. The research subjects were Madura University mathematics education study program students in semester 6. The instruments used included validator assessment sheets for learning devices, observation sheets of student activities during the learning process, observation sheets of lecturers' ability to manage learning, questionnaires sheets of student responses to the implementation of learning and test results learn. Based on the results of the study, there was an increase in student activity from 3.16 in cycle 1, 3.31 in cycle 2, to 3.67 in cycle 3. The learning outcome test also increased from 63.2% in cycle 1, 78.94% at cycle 2 becomes 89.47% in cycle 3. So it can be concluded that lesson study based multi-presentation learning can improve student learning outcomes in linear program subjects.